Distribution of Indoor Concentrations and Emission Sources of Formaldehyde in Japanese Residences - Shinohara, Naohide; Mizukoshi, Atsushi; Kataoka, Toshiyuki; Takamine, Koichi; Gamo, Masashi; Yanagisawa, Yukio (IntechOpen, 2011)
None